2022
DOI: 10.1177/17085381221084817
|View full text |Cite
|
Sign up to set email alerts
|

Depression screening in patients with vascular disease

Abstract: Objectives Major depression is associated with increased morbidity and mortality in vascular surgery patients. The US Preventive Services Task Force and American Heart Association recommend routine depression screening for adults, especially those with cardiovascular disease. Since routine depression screening has not been implemented in most vascular surgery clinics across the nation, we sought to determine the feasibility of depression screening and understand the prevalence and predictors of depression in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Screening for depression in patients with cardiovascular diseases is recommended by the US Preventive Services Task Force and the American Heart Association 133,134 . Furthermore, independent meta-analyses showed that psychotherapy/psychoeducation can have a preventive effect by reducing the severity of symptoms before the onset of depressive disorders [135][136][137] .…”
Section: Discussionmentioning
confidence: 99%
“…Screening for depression in patients with cardiovascular diseases is recommended by the US Preventive Services Task Force and the American Heart Association 133,134 . Furthermore, independent meta-analyses showed that psychotherapy/psychoeducation can have a preventive effect by reducing the severity of symptoms before the onset of depressive disorders [135][136][137] .…”
Section: Discussionmentioning
confidence: 99%